2007
DOI: 10.1111/j.1750-3841.2006.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Processing and Preservation on the Retention of Health‐Promoting Compounds in Broccoli

Abstract: In this work the effects of common household practices such as chilling, freezing, and cooking on vitamin C retention in broccoli (Marathon cv.), as well as their influence on the release of sulforaphane upon enzymatic hydrolysis of glucoraphanin by the endogenous enzyme myrosinase, were investigated. When chilled at 6 degrees C and 95% R.H. for 35 d, broccoli showed a vitamin C and sulforaphane loss of about 39% and 29%, respectively, while storage at -18 degrees C for 60 d resulted in similar losses, but mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 33 publications
6
42
0
1
Order By: Relevance
“…Considering such criterion, in horseradish a decrease of vitamin C of about 10% occurred after 60 days of storage for roots, young and mature leaves, and a loss of 50% was achieved at 10 months, with an estimated monthly loss of vitamin C of 5% for all tissues throughout the storage period. Similar results have been reported in the literature for other vegetables (Galgano et al, 2007;Howard et al, 1999;Wu et al, 1992). In root of horseradish, Kosson and Horbowicz (2008) recorded a vitamin C decline of about 20 -30% after 10 months of storage at 0 -1 °C, highlighting that the residual content could be considered still high ranging from 74 to 156 mg 100 g -1 fw.…”
Section: Effect Of Storage Conditions On Vitamin C Content Frozen Tissupporting
confidence: 77%
See 2 more Smart Citations
“…Considering such criterion, in horseradish a decrease of vitamin C of about 10% occurred after 60 days of storage for roots, young and mature leaves, and a loss of 50% was achieved at 10 months, with an estimated monthly loss of vitamin C of 5% for all tissues throughout the storage period. Similar results have been reported in the literature for other vegetables (Galgano et al, 2007;Howard et al, 1999;Wu et al, 1992). In root of horseradish, Kosson and Horbowicz (2008) recorded a vitamin C decline of about 20 -30% after 10 months of storage at 0 -1 °C, highlighting that the residual content could be considered still high ranging from 74 to 156 mg 100 g -1 fw.…”
Section: Effect Of Storage Conditions On Vitamin C Content Frozen Tissupporting
confidence: 77%
“…After harvest, many other factors influence the spoilage and vitamin C losses as the postharvest handling conditions, processing techniques and storage conditions (Davey et al, 2000;Galgano et al, 2002;Lee and Kader, 2000). In general, fresh fruits and vegetables contain more vitamin C than those stored (Galgano et al, 2007); thus, the vitamin C losses could be controlled within certain limits by using appropriate postharvest procedures to maintain as much as possible the compositional quality in plant foods. The processing techniques applied to food and vegetables, such as canning, freezing, and dehydration, to provide all-year-round availability of these foods can also result in significant losses of vitamin C. The extent of these losses is highly variable; losses of over 50% are typical for vegetables, but are much less for most fruits and in particular acid fruits (Davey et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, by 5 min steaming time sulforaphane levels were equivalent to those in unheated broccoli. Galgano, Favati, Caruso, Pietrafesa, & Natella (2007) on the other hand showed how sulforaphane production was dramatically higher in broccoli tissue following microwave cooking compared to boiling and steaming. It is clear from these studies that sulforaphane production can be significantly reduced during domestic cooking and therefore special care must be taken to optimize cooking practices to ensure adequate levels of bioactive isothiocyanates are present in the final cooked product.…”
Section: Introductionmentioning
confidence: 99%
“…This may include cutting, blanching, soaking or boiling. Moreover, mushrooms which are intended to be stored for a period of time (dried, frozen, pickled or canned) are often subjected to blanching, soaking or boiling (Galgano et al, 2007;Yao and Ren, 2011;Ahmed and Ali, 2013). Several previous studies have reported that treatments of vegetables, especially those above mentioned, where elevated temperature is involved, may lead to substantial changes in the chemical composition of mushrooms (e.g.…”
Section: Sampling and Preservation Treatments Of Agaricus Spp Mushroomsmentioning
confidence: 99%